Central Hypoventilation in Progressive Supranuclear Palsy. Issue 1 (19th May 2016) - Herrick, Kory S.; Woltjer, Randy; Pham, Thao; Chalupsky, Megan; Hiller, Amie L.
Abstract: Central hypoventilation, also known as Ondine's curse, results from an impairment of the autonomic respiratory drive. It is characterized by an attenuated or absent respiratory response to hypoxemia and hypercapnia with preservation of volitional respiratory function. R.J. was a 75‐year‐old woman with a diagnosis of probably PSP who developed central hypoventilation approximately 4 years after her initial onset of symptoms. Brain MRI showed no evidence of medullary lesions, one of the more common causes of adult‐onset central hypoventilation. The respiratory centers in the medulla, especially the ventral respiratory group (VRG) containing Botzinger and pre‐Botzinger complex of neurons, appear critical for normal respiratory rhythm generation. R.J. was maintained on a portable ventilator after her diagnosis of central hypoventilation. Ten months after being placed on ventilation, she passed of unclear causes. R.J. showed pathological features consistent with a diagnosis of PSP, specifically loss of neurons, secondary demyelination, and tau‐positive inclusions in both astrocytes and neurons, chiefly in the globus pallidus, midbrain, and brainstem. R.J. showed significant tauopathy in the region of the VRG in particular. We also examined this region in 16 other cases of PSP and found similar tauopathy in all but 1 case, which had significantly less involvement of this area. We had limited clinical data on these cases, but 1 had two episodes of unexplained hypoxia shortly before being placed on hospice. Central hypoventilation associated with tauopathy involving the VRG may be more common than often appreciated.